MODERN METHODS OF COMPETITIVENESS ASSESSMENT: THEORETICAL DISCOURSE - Medved, Yana (Socio-economic relations in the digital society, 2020)
The article examines the nature of the competitiveness of national economies and macroeconomic entities, how the competitiveness of different actors is measured and what modern methods allow to assess the competitiveness between different units of activity in geoeconomic activities. The article considers the phenomenon of competitiveness, how it is formed at different levels of financial and economic activity, how there has been a change in research methods of competitiveness from the first economic works to modern evaluation systems from leading scientific and financial institutions. The study of modern methods of assessing competitiveness concerned the three most influential world agencies and institutions such as the World Economic Forum, the World Bank and the International Institute for Management Development. Each of these institutions studies national economies according to its own developed criteria, which include both non-economic factors (political influence, social problems, the state of legislation) and financial and economic parameters (debt indicators, the state of forfeiting and credit services, the impact of government) . The study and analysis of modern methods of competitiveness assessment by international agencies allows to take into account all factors of economic activity of a country, to take into account all aspects of effective performance of the country with all the advantages and disadvantages leading to a certain assessment In general, the following results were obtained in the course of the research: the essence of the concept of «competitiveness», its main characteristics and features of formation in different conditions of economic activity are investigated; modern methods of competition assessment by international institutions and agencies are analyzed; systematized the main advantages and disadvantages of methodological tools for assessing competitiveness; the ways of elimination of key shortcomings, and also planning of effective activity of the country for increase of the rating are proved; accentuation of proposals on the use of positive and promising ideas to improve the rating of the Ukrainian economy at the global level.